2003
DOI: 10.1177/021849230301100308
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness and Coronary Artery Disease: An Indian Perspective

Abstract: To determine whether carotid intima-media thickness is associated with coronary artery disease and cardiovascular risk factors in the Indian population, carotid intima-media thickness was measured using high-resolution B-mode ultrasonography in 101 patients with coronary artery disease and 140 control subjects. Carotid intima-media thickness was measured at 3 predefined sites on each side. The maximum carotid intima-media thickness was significantly higher in the coronary disease group compared to the controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
2
26
0
2
Order By: Relevance
“…Visona and colleagues [25] showed that CIMT in CAD patients (1.45 ± 0.95) was significantly higher than in controls (0.87 ± 0.1; p < 0.005). Hansa et al [26] reported association of CIMT with CAD and CV risk factors in the Indian population, CIMT measured on each side, was significantly higher in the coronary disease group compared to the controls. In this respect, the results of present study (0.80 ± 0.22, 0.69 ± 0.13, p < 0.005) ( Table 2) are in agreement with previous studies showing a significant association between raised CIMT and the presence of CAD.…”
Section: Discussionmentioning
confidence: 97%
“…Visona and colleagues [25] showed that CIMT in CAD patients (1.45 ± 0.95) was significantly higher than in controls (0.87 ± 0.1; p < 0.005). Hansa et al [26] reported association of CIMT with CAD and CV risk factors in the Indian population, CIMT measured on each side, was significantly higher in the coronary disease group compared to the controls. In this respect, the results of present study (0.80 ± 0.22, 0.69 ± 0.13, p < 0.005) ( Table 2) are in agreement with previous studies showing a significant association between raised CIMT and the presence of CAD.…”
Section: Discussionmentioning
confidence: 97%
“…Asian Indians are reported to have three times higher rates of incidence and prevalence of CAD when compared with western populations, [1,2] leading to a greater social and economic impact. [3,4] Various factors, such as metabolic syndrome, diabetes, dyslipidemia and possible genetic predisposition are believed to contribute to this rising epidemic in India.…”
Section: Introductionmentioning
confidence: 99%
“…In India, Hansa G et al, 14 study was done in 2003 to determine whether CIMT is associated with CAD and cardiovascular risk factors in the Indian population. A total of 101 patients with CAD and 140 control subjects were assessed for CIMT and other conventional CVD risk factors.…”
Section: Resultsmentioning
confidence: 99%